# Tutor profile: Gabrielle W.

## Questions

### Subject: Pre-Algebra

8 + 12 ÷ 4

When simplifying, it's important to understand the order of operations: PEMDAS P = Parentheses E = Exponents M = Multiplication D = Division A = Addition S = Subtraction 1. First, simplify inside parentheses. 2. Next, evaluate exponents. 3. Then, multiply then divide from left to right. 4. Finally, add and subtract from left to right. Since we don't have any parentheses of exponents in this problem. We can skip right to rules 3 and 4: Note that MD comes before AS in PEMDAS So always do multiplication and division before Addition and subtraction When simplifying 8 + 12 ÷ 4, the order of operations tells us that we must first divide 12 by 4 before adding. 12 ÷ 4 is 3, so we have 8 + 3, which simplifies to 11.

### Subject: Basic Math

What percent of 65 is 37?

Finding a Percentage: A percentage is a standardized ratio that expresses a portion as a part of 100. To find what percentage of one number another is, you should divide the second number by the first and then multiply by 100 to find it as a percentage. To find what percent of 65 is 37, we begin by dividing 37 by 65. 37/65 = 0.5692308 We can round to the nearest hundredth and then multiply by 100. 0.5692 x 100 = 56.92% We now know that 37 is around 57% of 65.

### Subject: Algebra

1. Solve for x: X2 + x – 12 = 0

Writing the quadratic equation in the form ax2 + bx +c = 0 a = 1 b = 1 c = -12 Step 1: Find two numbers that multiply to give ac and add to give b. ac = 1 x -12 = -12 and b = 1 So we want two numbers that multiply together to make -12, and add up to give 1. 4 and -3 does that (4 x -3 = -12 and 4 + (-3) = 1 ) How to find 4 and -3? It helps to list the factors of ac = -12 and then try adding some to get b = 1 Factors of -12 include -1, -2, -3, 4, 6,12 4 and -3 add to give 1 and 4 x -3 = -12 Step 2: Rewrite the middle with those numbers: Rewrite x with 4x and -3x: X2 + 4x – 3x -12 = 0 Step 3: Factor the first two and the last two separately: The first two terms: x2 + 4x factor into x(x +4) The last two terms: -3x – 12 factor into -3(x+4) So we get: x(x+4) – 3(x+4) Step 4: The new terms should have a visible common factor (x+4) is the common factor to both terms: x(x+4) -3(x+4) Answer: (x-3) (x+4)

## Contact tutor

needs and Gabrielle will reply soon.